Validity and Reliability of the EduDeep Instrument: Measuring the Effectiveness of the ASOKA Approach in Deep Learning - Ahmad; Dani Irawan; Rizqi Fajar Pradipta (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2025)
The Teacher Professional Program is a strategic initiative that is highly relevant to President Prabowo's eight goals of strengthening human resource development, science, technology, and education. Ideally, PPG can shape students who are conscious, able to interpret learning contextually, and able to inspire all students through thinking, feeling, tasting, and exercising so that graduates become professional teachers. However, students are still trapped in conventional learning that focuses on fulfilling formal formats, so the essence of meaningful learning has not been optimized. The ASOKA approach is a new approach as a solution to solve PPG student learning problems, including to improve PPG students' competence in designing meaningful learning. Therefore, the objectives of this study are to: (1) Analyze PPG students' perceptions of deep learning through the ASOKA approach. (2) Analyze the effectiveness of the ASOKA approach in helping PPG students design meaningful learning. An exploratory quantitative research approach was chosen with a research period from April 2025 to December 2025, involving 100 students selected through purposive sampling. Data was collected from the distribution of test instruments and questionnaires. The collected data was then analyzed inferentially using Principal Component Analysis, which was operated using JASP software version 19.3.